2017
DOI: 10.1111/apa.13940
|View full text |Cite
|
Sign up to set email alerts
|

Using quality improvement to decrease birth asphyxia rates after ‘Helping Babies Breathe’ training in Kenya

Abstract: Aim: The Helping Babies Breathe (HBB) programme is known to decrease neonatal mortality in low-resource settings but gaps in care still exist. This study describes the use of quality improvement to sustain gains in birth asphyxia-related mortality after HBB.Methods: Tenwek Hospital, a rural referral hospital in Kenya, identified high rates of birth asphyxia (BA). They developed a goal to decrease the suspected hypoxic-ischaemic encephalopathy (SHIE) rate by 50% within six months after HBB. Rapid cycles of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…This is because babies who were thought to be stillborn were recognised as being depressed and staff realised they had the potential to survive with basic HBB resuscitation. The study by Rule et al (6) did not report rates of stillbirths, delivery room deaths or survivor morbidity, and the authors agreed that this was an important area for future study. Other studies have been reassuring about morbidity rates, as they have shown that babies who needed resuscitation from low-income and middle-income countries did not have an excess of neurological or developmental morbidity at 12 months of age (9,10).…”
Section: Helping Babies Breathe Can Reduce Deaths With the Right Combmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because babies who were thought to be stillborn were recognised as being depressed and staff realised they had the potential to survive with basic HBB resuscitation. The study by Rule et al (6) did not report rates of stillbirths, delivery room deaths or survivor morbidity, and the authors agreed that this was an important area for future study. Other studies have been reassuring about morbidity rates, as they have shown that babies who needed resuscitation from low-income and middle-income countries did not have an excess of neurological or developmental morbidity at 12 months of age (9,10).…”
Section: Helping Babies Breathe Can Reduce Deaths With the Right Combmentioning
confidence: 99%
“…The study by Rule et al (6) in this issue of Acta Paediatrica describes a rural Kenyan hospital health professional team's use of quality improvement (QI) techniques to decrease hypoxic ischaemic encephalopathy rates by 50% within six months of HBB training. In the previous five years, this hospital had tried to adopt the American Academy of Pediatrics' Neonatal Resuscitation Programme twice, but could not sustain the initiative due to a lack of trained local facilitators, simulators and planning for ongoing recertification.…”
Section: Helping Babies Breathe Can Reduce Deaths With the Right Combmentioning
confidence: 99%
See 1 more Smart Citation
“…QI strategies have been shown in several single-center studies to be successful in decreasing maternal and neonatal morbidity and mortality (40,42,(47)(48)(49). The power of training followed by a commitment to QI was exemplified in Nepal, where formation of QI teams, development of QI goals, HBB trainings, daily skill checks, and refresher trainings resulted in the intrapartum stillbirth rate decreasing from 9.0 to 3.2 per thousand deliveries, and 24-h neonatal mortality decreasing from 5.2 to 1.9 per thousand live births (42).…”
Section: Ongoing Improvement For the Care Of Mothers And Babiesmentioning
confidence: 99%
“…Both approaches have been shown to be successful in improving aspects of quality in healthcare. [6][7][8][9] QA helps health managers define clinical guidelines and standardise procedures, thus making concrete steps towards improving quality of care. QA promotes confidence, improves communication and improves understanding of what is needed, within the health system, to improve quality of care.…”
Section: Introductionmentioning
confidence: 99%